KATHAK DANCE OF BANARAS GHARANA: A HISTORICAL PERSPECTIVE - Mishra, Sanjeev Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Banaras Gharana of Kathak is one of the principal stylistic schools of North Indian classical dance, known for its distinctive repertoire, aesthetic, and lineage-based transmission of knowledge. Rooted in the sacred city of Varanasi, the Banaras Gharana has historically played a significant role in preserving and shaping the Kathak tradition. Despite its cultural and historical importance, comprehensive academic studies specifically focused on this gharana—especially its genealogy and present status—remain limited.